1972
DOI: 10.1159/000252133
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of a Sunscreen upon the Lysosomes of Ultraviolet-Irradiated Skin

Abstract: It has been generally accepted in the literature that the substituted benzophenones, having wide-spectrum ultraviolet absorbing properties, provide excellent protection from the harmful effects of sunburn. Evidence is here presented which indicates that release of lysosomal acid phosphatase and acid protease was facilitated in cultured human foreskin and rodent skin in vivo after exposure to UV radiation, without protection by 10% sulisobenzone. Under these experimental conditions, there occurred in human fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1975
1975
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Skin was taken 72 h after treatment with sodium laurate in each case. rupture and enzyme release was found during the first 24 h of the response, in contrast to the reaction of skin to ultraviolet light in which there is histochemical and biochemical evidence for acid phosphatase release (Fand, 1972;Johnson, 1968;Johnson & Daniels 1969;Volden, 1978). Sodium laurate did cause sufficient initial damage (Prottey et al, 1978), however, to elicit a repair response and it is this which gave rise to the principal alteration in acid phosphatase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin was taken 72 h after treatment with sodium laurate in each case. rupture and enzyme release was found during the first 24 h of the response, in contrast to the reaction of skin to ultraviolet light in which there is histochemical and biochemical evidence for acid phosphatase release (Fand, 1972;Johnson, 1968;Johnson & Daniels 1969;Volden, 1978). Sodium laurate did cause sufficient initial damage (Prottey et al, 1978), however, to elicit a repair response and it is this which gave rise to the principal alteration in acid phosphatase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In skin irritation, the epidermal response usually involves varying degrees of cellular damage followed by a repair phase in which growth is stimulated (Prottey & Hartop, 1973;Middleton & Pratt, 1978) and this often leads to exaggerated differentiation in the form of thickening of the granular layer (Reid & Jarrett, 1967;Cowan & Mann, 1971). Biochemical and histochemical studies of the response to the physical stimulus of ultraviolet light (Fand, 1972;Johnson, 1968;Johnson & Daniels, 1969;Volden, 1978) suggested that cellular injury was associated with release of acid phosphatase from the epidermis, while a histochemical study of the hyperplastic response to vitamin A demonstrated that epidermal repair was associated with an increase in acid phosphatase (Reid & Jarrett, 1967). The present study was undertaken to examine changes in acid phosphatase activity at all stages of the reaction to a chemical irritant, sodium laurate.…”
mentioning
confidence: 99%
“…The enzyme values were decreased in the irradiated epidermis compared with the non-irradiated epidermis of control suction blisters, but the values found in the fluid of irradiated blisters were not decreased compared with control fluid.There is evidence that lysosomes are involved in the events which follow ultraviolet irradiation. Decreased total acid phosphatase activity has been demonstrated in whole skin homogenates following moderately high doses of middle-wavelength ultraviolet radiation (UV-B) (Johnson, 1968;Fand, 1972). The primary event leading to common sunburn is thought to be in the epidermis, since the erythemogenic rays penetrate into the epidermis (Fitzpatrick et al, 1963; Everett et al, 1966).…”
mentioning
confidence: 99%